Raman amplification-based WDM-PON architecture with centralized Raman pump-driven, spectrum-sliced erbium ASE and polarization-insensitive EAMs - Lee, Ju Han; Han, Young-Geun; Lee, Sang Bae (OPTICAL SOC AMER, 2006)
We propose a novel wavelength division multiplexed (WDM) passive optical network (PON) architecture based on the distributed Raman amplification and pump recycling techniques, which features fully bidirectional transmission, relaxed signal power margin, and active light source-free, colorless subscriber units. The reuse of non-negligible residual Raman pump power as a pump for an erbium fiber-based upstream broadband ASE source allows for fully-centralized control of light sources at optical network units (ONUs), while distributed Raman amplification over a transmission link enables us to obtain lossless low power signal transmission. Furthermore, low-cost and colorless ONUs can be realized by use of the Raman pump-recycled erbium ASE and polarization-insensitive electroabsorption modulators. Error-free upstream transmission over a 50 km fiber link is successfully achieved at a data rate of 622 Mbit/s. (c) 2006 Optical Society of America
Keywords: AMPLIFIER LIGHT-SOURCE; SYSTEMS; PERFORMANCE; DISPERSION; NETWORK